Optimization Of Assembly Line Using Discrete Event Simulation - Shah Fenner Khan, Nurdiyanah Nasuha (2019)
Nowadays, competition has become more intense for the manufacturing companies than the previous decades. However, many still struggling to increase their quality and the productivity level while keeping the cost at minimum. Thus, in order to stay competitive, manufacturers are expected to develop a sense of commitment towards continuous improvement, and it is important for a company to increase their productivity level. Furthermore, it is vital to increase the productivity level of an assembly line in a manufacturing company as it plays a critical role in obtaining a high quality while keeping the cost at minimum. The productivity level of an assembly line depends on the balancing performance. Moreover, a simulation software was used to foresee the assembly line performance before actual implementation. Therefore, line balancing technique were used to improve the assembly line by assigning the workstations evenly by satisfying the constraint provided. This project aims are to minimize the cycle time of an assembly line using line balancing technique and discrete event simulation. The assembly chosen are the spring adjustment screw assembly, SAS TS83, SAS TS92 and SAS TS93. The data were collected using the time study method. Then, the line balancing technique were used to distribute the task evenly among the workstations. The result which has been gathers from the line balancing technique were then transfer to simulation software in order to enhance the result. The simulation software used in this project is Delmia Quest simulation software. Henceforward, What-if analysis were used to explore and compare various scenarios, based on changing conditions of the assembly line. The use of both line balancing technique and discrete event simulation software shows an improvement in the cycle time and the efficiency of the assembly line from 12.128 seconds to 10.135 seconds, and increase roughly by 14% respectively. Moreover, two different scenarios were proposed, which the first scenario is develop by combining SAS TS92 and SAS TS93 into one workstation, due to they both have the same operating procedures. The second scenarios is by increasing the output produced and thus minimize the cycle time of the assembly for SAS TS92.